Relationship between Trauma Exposure and Psychological Resilience among University Students in Ghana: A Quantitative Analysis - King-Kuadzi, Kingsley Eyram (Journal of Advanced Psychology, 2025)
Purpose: This study aims to investigate the impact of trauma exposure on psychological resilience among university students in Ghana, highlighting the significance of coping strategies in mitigating the effects of trauma. Methodology: A cross-sectional design was employed from August 2024 to March 2025, utilising a structured questionnaire distributed through social media platforms. Data were collected from 158 participants and analysed using SPSS to summarise demographic information, levels of trauma exposure, and resilience. Findings: The results indicated a significant negative correlation between trauma exposure and psychological resilience (r = -0.252, p = 0.001), suggesting that higher levels of trauma exposure are associated with lower resilience. Gender did not significantly affect resilience outcomes, and age was not a predictive factor. However, coping strategies emerged as critical mediators, significantly enhancing resilience among participants. Unique contribution to theory, practice and policy: This study confirms that trauma exposure adversely impacts psychological resilience in Ghanaian university students, emphasising the need for targeted mental health interventions. While demographic factors like gender and age were not influential, the role of effective coping strategies highlights the importance of developing adaptive mechanisms to bolster resilience. Future research should focus on identifying and implementing the most effective coping strategies to improve resilience in this vulnerable population.